Efektivitas Kunjungan Nifas, Motivasi Ibu dan Peran Keluarga terhadap Pengurangan Nyeri Perineum di Wilayah Kerja Puskesmas Desa Kairatu: The Effectiveness of Postpartum Visits, Mother's Motivation and Family Role in Reducing Perineal Pain in the Work Area of ​​the Kairatu Village Health Center - Jeni Aurima (Jurnal Interprofesi Kesehatan Indonesia, 2023)
Introduction: The postpartum period (Puerperium) is the period when the placenta comes out and usually this postpartum period only lasts approximately 6 weeks or 40 days. Puerperium is from the word Puer which means baby and Parous gives birth, so Puerperium means the period after giving birth to a baby and the period when the uterine organs return to their pre-pregnancy pre-pregnancy state. Objectives: This study aims to determine the Effectiveness of Postpartum Visits, Mother's Motivation and Family roles in Reducing Perineal Pain in the Kairatu Health Center area, West Seram Regency in 2021. Method: The type of research used is quantitative with descriptive techniques that provide an overview of the effectiveness of care during postpartum visits and the physical discomfort that exists during the postpartum period. The research instrument used in the research was a questionnaire to determine the effectiveness of postpartum visits, the role of the family and the reduction of physical discomfort to perineal pain. In this research, the number of samples taken was a total of 35 postpartum women with the accidental sampling technique used. Data collection by filling out a questionnaire and analyzing using univariate and bivariate analysis with Chi-Square testing. Result: Based on the results of data processing in this study, it shows that postpartum visits have a p-value or significance of 0.000 which is an area where the hypothesis is accepted, namely p-value ≤ 0.05. Conclusion: It can be concluded that postpartum visits are effective in reducing perineal pain.